Real wages and local unemployment in the euro area - Anna Sanz de Galdeano; Jarkko Turunen (European Central Bank (ECB), 2005)
We present empirical evidence of the extent of wage rigidity in the euro area and European countries derived from longitudinal data on individuals. Wage rigidity is measured by the elasticity of individual real wages with respect to local unemployment. The results suggest that the elasticity is indeed negative, i.e. that real wages are lower in local labour markets with higher unemployment. The size of the elasticity for the euro area is similar to that found in previous studies for a number of countries, including the United States. Furthermore, there is some variation in the unemployment elasticity by worker groups and along the wage distribution. In particular, public sector wages are relatively rigid compared to wages in the private sector, contributing significantly to wage rigidity in the euro area. Country results show some heterogeneity in wage rigidity across European countries and suggest a tentative ranking of countries.
Keywords: E24; J45; J64; 330; local unemployment; panel data; real wages; wage curve; Reallohn; Lohnrigidität; Arbeitslosigkeit; Schätzung; EU-Staaten